The profile of occupational stress in a sample of health profession academics at a historically disadvantaged university in South Africa - Simons, A.; Munnik, E.; Frantz, J.; Smith, M. (South African Journal of Higher Education, 2019)
Background: Higher education is a high stress occupation or environment. Academics in health professions are engaged in professional training that adds clinical or profession-specific competencies to general academic and research outcomes. Academics in health professions assume many roles and must remain current in the practise of their professions that increases stress. Studies on occupational stress amongst health professions academics are lacking in the South African context. Objectives: To assess occupational stress in a sample of Health profession academics at a Historically Disadvantaged Institution (HDI). Methods: An online survey was conducted with a randomly selected sample of 51 permanent academics. The response rate was 55% after incentives and reminders. Instruments included a demographic questionnaire, Assessing emotions scale and the Sources of Work Stress Inventory. Descriptive statistics, correlation and regression were used to analyse the data. Instruments were reliable with this sample. Ethics clearance was obtained (Reg. No.: 15/4/42) and all ethics principles were upheld. Results: The sample was mostly female and the composition was consistent with the profiles of the faculty, health professions and HDIs. Small effects were reported for associations between demographics, EI and Occupational stress. Mixed results were reported for predictive relationships. EI and level of education were predictive of certain sources of occupational stress. Conclusion: Transformations and the work environment contributed to academics experiencing occupational stress. The historical apartheid legacies still manifest in patterned ways along gender, race and professional status in the occupational stress academics experience. Health professionals constitute a legitimate subgroup that impacts the experience and management of occupational stress. EI is an important factor to consider in the experience and management of occupational stress.